Development of PMC Numerical Model for Soil and Stone Mixture - Zhili Sui; Zhaoguang Li; Yanhua Gao; Yuan Li; Yiwu Zheng; Yuan Meng (Advances in Civil Engineering)
Soil and stone mixture is widely distributed in China, and its physical and mechanical properties are complex, which has a significant impact on geotechnical engineering. Usually soil and stone mixture shows anisotropic features along or perpendicular to the direction of settled layers, and the strength will be significantly affected by intermediate principal stress. True triaxial tests were carried on, Paul–Mohr–Coulomb (PMC) failure criterion was used for the strength analysis in soil-stone mixture, and related parameters of PMC model were obtained. A user-defined PMC numerical constitutive model was developed for FLAC3D. Composite failure criteria of shear failure and tension cut-off were applied for numerical analysis, and nonassociated flow rule was proposed based on the Mohr–Coulomb model. Verification modelling was applied as well, and deviation between analytical and numerical solutions in strains of X direction, Y direction, and Z direction was 1.0013, 1.0003, and 1.002, respectively.